Ultrahigh-speed clock recovery with optical phase lock loop based on four-wave-mixing in a semiconductor optical amplifier - Kim, DH; Kim, SH; Jo, JC; Choi, SS (ELSEVIER SCIENCE BV, 2000)
A new phase lock loop (PLL) is proposed and demonstrated for clock recovery from 40 Gbps time-division-multiplexed (TDM) optical signal using simple optical phase lock loop circuit. The proposed clock recovery scheme improves the jitter effect in PLL circuit from the clock pulse laser of harmonically-mode locked fiber laser. The cross-correlation component between the optical signal and an optical clock pulse train is detected as a four-wave-mixing (FWM) signal generated in SOA. The lock-in frequency range of the clock recovery is found to be within 10 KHz. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: LASER-DIODE AMPLIFIER; SIGNAL